Interconnection and differentiation between human rights law and international humanitarian law - AHMED, RUBAR MAJEED (Journal of Legal and Political Studies, 2024)
This research focuses on the relationship between Human Rights Law and International Humanitarian Law, despite the clear differences between them in terms of scope and application. While Human Rights Law is applied during both peace and war times, International Humanitarian Law is only applicable in situations of international and non-international armed conflicts.In terms of sources, Human Rights Law relies on global documents such as the Universal Declaration of Human Rights (1948), the two International Covenants on Human Rights (1966), and regional treaties, while International Humanitarian Law is based on the Four Geneva Conventions of 1949 and their additional protocols, and lacks specific regional rules. Furthermore, the implementation of some human rights provisions can be suspended in times of emergency, while International Humanitarian Law cannot be suspended because it is an emergency law by nature. International Humanitarian Law has an older history compared to Human Rights Law. However, both share the fundamental goal of protecting human dignity, which is a part of natural law, and both require states to incorporate their provisions into national legislation for practical application.Although both laws share an imperative nature and promote individual rights, the central question this research addresses is: What prompted the creation of International Humanitarian Law to protect individuals during armed conflicts, despite the fact that Human Rights Law already provides protection in both peace and war? This is the question the research seeks to answer. Keywords: the rights, the relationship, human being, the scope
Keywords: the rights; the relationship; human being; the scope